The Algebra of Semigroups of Sets - Aigner, Mats; Chatyrko, Vitalij A.; Nyagahakwa, Venuste (MATHEMATICA SCANDINAVICA, 2015)
We study the algebra of semigroups of sets (i.e. families of sets closed under finite unions) and its applications. For each $n > 1$ we produce two finite nested families of pairwise different semigroups of sets consisting of subsets of $\mathsf{R}^n$ without the Baire property.